UNDANG-UNDANG NOMOR 13 TAHUN 2012 TENTANG KEISTIMEWAAN DAERAH ISTIMEWA YOGYAKARTA DALAM PERSPEKTIF POLITIK HUKUM BERPARADIGMA PANCASILA - , Diasma Sandi Swandaru, S.Sos; , Aminoto, SH., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research has purpose to identify the values of Pancasila in the Law Number 12 of 2011 regarding the Formation of Law and Regulation. Reformation brings forth a change in law and regulation formulation away from Pancasila values. Legal political change on regional governance law and regulation has impact on the practice and implementation of regional governance, including the regional governance of Kasultanan Yogyakarta and Paku Alaman that since the independent day united to Republic Indonesia as special region in the Unitary State Republic of Indonesia. This research is conducted in Yogyakarta and Jakarta and focus on the implementation of Pancasila values in the Law Number 13 of 2012 regarding Features of Yogyakarta Special Region. Data of this research is obtained from primary and secondary source. Primary source is data obtained from direct interview with stakeholder and secondary source is data obtained from Law, judicial minutes and literatures. The data is analyzed by using descriptive qualitative methods. This research concludes that the values of Pancasila implemented in the principles within Law Number 12 of 2011 and operationally translated into legal norms in the Law Number 12 of 2012. Democratic, unity and just values are the main element supported by divinity and humanity value as an impartial unity in the formation and content of Features of Yogyakarta Special Region Law. The formation of law and regulation as the formation of Features of Yogyakarta Special Region Law shall be a model of law and regulation formation with Pancasila paradigm as Staatsfundamentalnorm and the source of all legal sources in Indonesia